AN INVESTIGATION INTO PARENTS’ SOCIO-ECONOMIC STATUS AND ITS IN-FLUENCE ON ACADEMIC PERFORMANCE OF JUNIOR HIGH SCHOOL PUPILS IN THE AOWIN MUNICIPALITY IN GHANA - AFFUL, KINGSLEY (International Journal of Multidisciplinary Research and Studies, 2019)
This study was conducted in Aowin municipality. It investigated the socio-economic background of parents in relation to the academic performance of pupils. A descriptive survey design using mixed-methods sequential explanatory approach was employed for this study. Simple random and convenience sampling methods were used to select 126 participants for the study. Questionnaire and structured interview guide were the main instruments used for the collect data. The quantitative data were analyzed and presented in tables as frequencies, percentages, mean and standard deviation while the qualitative data was analyzed thematically. Inferential statistics was computed using Spear man’s rho correlation test via Statistical Product for Services Solution (SPSS) software at a significance level of p ≤ .05 using a confidence interval (C.I) of 95%. The study revealed that of public basic school pupils in the Aowin municipality were average and below average academic achievers who came from poor socio-economic background. Poor attitudes of parents towards the education of their wards significantly contributed to poor or low academic performance of the pupils. It was recommended, among others, that parents should adequately provide for the basic and school needs of their wards. They should also motivate and encourage pupils to always attend school.